2020
DOI: 10.1111/jebm.12407
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of bleeding from esophageal varices in patients with liver cirrhosis: An update and review of the literature

Abstract: All patients with liver cirrhosis and portal hypertension should be stratified by risk groups to individualize different therapeutic strategies to increase the effectiveness of treatment. In this regard, the development of primary prophylaxis of variceal bleeding and its management according to the severity of portal hypertension may be promising. This paper is to describe the modern principles of primary prophylaxis of esophageal variceal bleeding in patients with liver cirrhosis. The PubMed and EMbase databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 108 publications
1
16
0
2
Order By: Relevance
“…These limitations have contributed to the development of alternative methods of assessing PH severity. Several biochemical tests and serum concentrations of inflammatory biomarkers, as well as imaging techniques, have been reported to correlate with CSPH [2]. Adequate diagnosis of PH is important, however early diagnosis of subclinical PH is even more important, because of the preprimary prophylaxes that include etiotropic and pathogenetic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations have contributed to the development of alternative methods of assessing PH severity. Several biochemical tests and serum concentrations of inflammatory biomarkers, as well as imaging techniques, have been reported to correlate with CSPH [2]. Adequate diagnosis of PH is important, however early diagnosis of subclinical PH is even more important, because of the preprimary prophylaxes that include etiotropic and pathogenetic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The review by Garbuzenko et al [ 38 ] confirmed that staging the severity of PH in cirrhotic subjects and personalized preventive therapy could lead to an increase in both patient survival and treatment effectiveness; particularly, DAAs achieve the amelioration of subclinical PH. In a recent study by Afdhal et al [ 39 ] of 50 patients with clinically significant PH (presence of esophageal varices, HVPG > 6 mmHg) from different international centers, 89% obtained a HVPG reduction of > 20% and only 3 patients obtained a reduction of portal pressure to less than 12 mmHg.…”
Section: Direct-acting Antiviral Agents and Liver Cirrhosis Related Eventsmentioning
confidence: 99%
“…ассоциированном с хронической HBVи HCV-инфекцией За последние годы установлено, что УВО при ассоциированном с хронической HBV-и HCV-инфекцией ЦП позитивно влияет не только на гистологическую структуру печени, но и на динамику ПГ [44]. Например, S. Manolakopoulos и соавт.…”
Section: влияние устойчивого вирусологического ответа на портальную гипертензию при циррозеunclassified